Imagining England's past inspiration, enchantment, obsession - Owens, Susan 19XX- (Thames & Hudson, 2023)
England has long built its sense of self on visions of its past. What does it mean for medieval writers to summon King Arthur from the post-Roman fog; for William Morris to resurrect the skills of the medieval workshop and Julia Margaret Cameron to portray the Arthurian court with her Victorian camera; or for Yinka Shonibare in the final years of the twentieth century to visualize a Black Victorian dandy? By exploring the imaginations of successive generations, this book reveals how diverse notions of the past have inspired literature, art, music, architecture and fashion. It shines a light on subjects from myths to mock-Tudor houses, Stonehenge to steampunk, and asks how - and why - the past continues so powerfully to shape the present. Not a history of England, but a history of those who have written, painted and dreamed it into being, Imagining England's Past offers a lively, erudite account of the making and manipulation of the days of old.
Keywords: Künste; Rezeption; Vergangenheit; Großbritannien